Green Synthesis of Silver Nanoparticles from Indonesian Medicinal Plants: Antibacterial and Biomedical Applications - Fitra Adi Prayogo; Mellyaning Oktaviani Sonya Kirana Sari; Muhammad Badrul Huda (Universitas Diponegoro, 2026)
Objectives. Antimicrobial resistance is among the most pressing global health threats, and green synthesis of silver nanoparticles (AgNPs) from plant extracts offers a low-cost, low-toxicity route to new antibacterial agents. This review consolidates and critically evaluates the evidence on AgNPs synthesised from Indonesian medicinal plants, covering their biochemistry, antibacterial performance, biomedical applications, and environmental sustainability. Methods. A semi-systematic review was conducted following PRISMA-2020 reporting. Five international and Indonesian databases were searched for peer-reviewed studies (2015–2025) on plant-mediated AgNP synthesis characterised by at least one standard technique, with study quality appraised against a six-domain checklist. Findings. Plant-mediated AgNPs of 5–50 nm with surface plasmon resonance bands at 400–460 nm have been successfully produced from Moringa oleifera, Curcuma longa, Areca catechu, Piper betle, and several endemic Indonesian species. Antibacterial action against Gram-positive cocci (including methicillin-resistant Staphylococcus aureus) and Gram-negative rods proceeds mainly through membrane disruption, Ag⁺ release, reactive-oxygen-species generation, and DNA interaction; smaller, phenolic-capped particles tend to be more potent. Plant-mediated routes also score markedly better than conventional chemical synthesis on green-chemistry metrics. Gaps. Most studies test only standard laboratory strains rather than clinical multidrug-resistant isolates; in vivo data, raw-material standardisation, and ecotoxicological testing remain scarce. Prospects. Future Indonesian work should standardise plant material, adopt harmonised antibacterial and bio-nano reporting protocols, integrate ecotoxicological screening at the bench stage, and pursue coordinated programmes that bridge laboratory synthesis and clinical translation